S–CO2 cooling heat transfer mechanism based on pseudo-condensation and turbulent field analysis. (1st January 2023) - Fan, Y.H.; Tang, G.H.; Sheng, Q.; Li, X.L.; Yang, D.L.
Abstract: The supercritical-CO2 (S–CO2 ) cooler is one of the main components in S–CO2 power system. This work aims at revealing the cooling mechanism of S–CO2 under wide working conditions to assist the S–CO2 cooler design. The pseudo-condensation is proposed with the analogy between supercritical cooling and subcritical condensation. From the pseudo-condensation and the traditional turbulent field analysis, the specific heat is found to be the dominant parameter for the enhanced heat transfer in S–CO2 cooling. The disappearing of enhanced cooling heat transfer, in the view of pseudo-condensation, is mainly due to the thickening of pseudo liquid film, which is dominated by the gravity force, inertial force and interfacial force in low mass flux flow while the gravity force effect is negligible in high mass flux flow. However, from the turbulent field analysis, the disappearing of enhanced cooling heat transfer is mainly caused by the thickening boundary layer due to the local increase in density and viscosity in addition to the decrease in specific heat. Finally, based on the S–CO2 cooling mechanism, two correlations for predicting heat transfer are proposed and evaluated. The present work can significantly enhance in-depth understanding on S–CO2 cooling and promote engineering application. Highlights: The S–CO2 cooling mechanism is analyzed with pseudo-condensation and turbulent field. Pseudo-condensation is based on analogy between supercritical cooling and subcritical condensation. Turbulent field analysis focuses on selection of key influencing thermophysical properties. Two more accurate correlations are developed based on the obtained cooling mechanism. The pseudo-condensation for S–CO2 cooling process is proved to be with high reliability.